2017
DOI: 10.1080/10495398.2017.1379415
|View full text |Cite
|
Sign up to set email alerts
|

Two New Insertion/Deletion Variants of the PITX2 Gene and their Effects on Growth Traits in Sheep

Abstract: In China, Tong sheep (TS) and Lanzhou fat-tailed sheep (LFTS) are two closely relative endanger breeds for low meat production and low fecundity, finding some marker-assisted selected (MAS) is our first priority for improving their growth traits. For this purpose, Hu sheep (HS) and small-tailed Han sheep (STHS) were compared with two endangered breeds (TS and LFTS). Paired-liked homeodomain transcription factor 2 (PITX2) gene was the important member of PITX family, which could adjust animal growth through hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…MAS is the most common method in molecular breeding. Especially indel has been widely reported in animal breeding for potential MAS (Ren et al, 2017;Cui et al, 2018;Zhao et al, 2018;Kang et al, 2019;Yang et al, 2019). Therefore, we aimed to determine the relationship between the indel polymorphism within the CDC25A and growth traits in goat.…”
Section: Discussionmentioning
confidence: 99%
“…MAS is the most common method in molecular breeding. Especially indel has been widely reported in animal breeding for potential MAS (Ren et al, 2017;Cui et al, 2018;Zhao et al, 2018;Kang et al, 2019;Yang et al, 2019). Therefore, we aimed to determine the relationship between the indel polymorphism within the CDC25A and growth traits in goat.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several reports have shown that mutations in introns can have a significant impact on livestock and poultry production. Two indel mutations in the intronic region of the ovine PITX2 gene have been found to have significant effects on ovine growth traits (Zhao et al ., 2017). A 15-bp indel on the intron of HIAT1 is detected to be relevant to the growth traits of goats and could be used for MAS as a molecular marker in goat populations (Gao et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The body weight (BW), body height (BH), body length (BL), chest circumference (ChC), chest depth (ChD), chest width (ChW), hucklebone width (HuW), hip width (HW), and cannon circumference (CaC) were reported using standard measurement method [ 25 ]. Consequently, body length index (BLI), chest circumference index (ChCI), chest width index (ChWI), cannon circumference index (CaCI), hucklebone width index (HuWI), and trunk index (TI) were calculated [ 26 ].…”
Section: Methodsmentioning
confidence: 99%